DESAIN RENCANA AKSI DAERAH BERBASIS KOLABORASI PEMERINTAH, DUNIA USAHA, DAN MASYARAKAT DALAM PENGUATAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Muhammad Lukman Hakim (Universitas Serang Raya, 2025)
Problems: The implementation of Corporate Social Responsibility (CSR) at the regional level has shown significant progress, but is not yet fully focused on supporting the sustainable development agenda. Many CSR programs are fragmented, not aligned with regional planning documents, and are not managed through collaborative mechanisms that equally involve government, businesses, and communities. Purpose: To provide a description and analysis of how government, businesses, and communities collaborate to strengthen corporate social responsibility. Methodology: This study uses a qualitative approach through document analysis, literature review, and conceptual modeling to formulate a Regional Action Plan (RAD) design based on multi-stakeholder collaboration. Findings: The research findings indicate that strengthening coordination between actors, data system integration, and social accountability mechanisms are key prerequisites for the effectiveness of the CSR RAD. The resulting design positions local governments as the driving force behind orchestrating collaboration, enabling CSR to be more focused, inclusive, and provide tangible benefits to the community. Research Type: Qualitative Keywords: corporate social responsibility, regional action plan, collaborative governance